Reappraisal of the genus Visia (Batrachospermales, Rhodophyta) and proposal for a new genus and species - Necchi, Orlando [UNESP]; Entwisle, Timothy J.; Lopes, Yasmin M. Silva [UNESP]; Vis, Morgan L. (Taylor & Francis, 2024)
The genus Visia is reappraised based on new morphological and molecular data (rbcL and COI-5P sequences), from recently collected and previously studied materials, resulting in the need for several taxonomic changes. Based on our phylogeny and sequence divergence, the genus Visioidea gen. nov. is proposed for two samples from Brazil, forming a distinct clade that is morphologically undistinguishable from the generitype of Visia (V. cayennensis). Two lineages of Visia with high genetic divergences from other species are proposed as new species: 1) V. verviridis sp. nov. from Australia; 2) V. amazonensis sp. nov. from Brazil. Although genetically distinct, both species are morphologically very similar to V. cayennensis. A new record of V. cylindrocellularis was found in Australia, expanding the geographic distribution and the morphometric ranges for this species. The number of species currently recognized in Visia is now six, four with DNA sequence data and two identified based solely on morphology (V. longiarticulata and V. turgida). Cryptic genera within the order Batrachospermales were not recognised until recently with the proposals of Volatus, morphologically indistinct from Kumanoa, and Macrosporophycos undistinguishable from Montagnia and here a third cryptic genus Visioidea is described.
Keywords: Batrachospermales; COI-5P; cryptic species; Freshwater Red Algae; rbcL; Revision; Systematics